Drawing in the Land Rock Art in the Upper Nepean, Sydney Basin, New South Wales - Dibden, Julie (Terra Australis, 2019)
"Drawing in the Land offers an important contribution to the field of rock art research and Australian archaeology. It provides a detailed study of the previously under-examined rock art of the Hawkesbury/Nepean area of New South Wales. The study presents a detailed historiography of Australian rock art research and, through the lens of landscape archaeology, offers an innovative contribution to rock art studies in the wider Sydney Basin. The volume's theoretical focus on materiality, embodied practice and performance allows for the charting of ideational change and provides a unique contribution to the late Holocene archaeology of NSW and contact archaeology within Australia more broadly."